Optical and Morphological Studies of Doped Y2O3 Nanostructures - Kumar, Deepak (My University, 2016)
The present work deals the optical and morphological properties of lanthanides (RE3+ = Eu3+ , Tb3+ and Dy3+) doped Y2O3 nanophosphors prepared via co-precipitation method. Various techniques were used to enhance the PL characteristics of doped Y2O3 nanophosphors. Study of alkali metal ions (Li+ , Na+ , and K+ ) co-doping with Y2O3:RE3+ have been done. The main factors which affect the photoluminescence emission of the prepared phosphors are described in detail. Effect of various surfactants/polymers on optical and morphological properties of RE3+ doped Y2O3 have also been studied in detail. Chapter 1 portrays the introduction of rare earth doped nanostructures. This chapter covers the various important topics explaining luminescence phenomenon of nanophosphors. Moreover, introduction to luminescence in lanthanide doped material have also been described in this chapter. At the end of this chapter a brief introduction of host Y2O3 and its applications in various fields of science is presented. In Chapter 2, reported work which describes synthesis, structural, optical and photoluminescence (PL) studies of doped Y2O3 is reviewed. Effect of various parameters that affect the optical and morphological properties of Y2O3 has been described in detail. Besides this, other techniques developed to enhance the PL emission intensity has also been discussed. At the end of the chapter, the reasons for selecting main objectives behind this work are presented. Chapter 3 describes the details of the synthesis procedure to prepare doped Y2O3 nanophosphors (NPs) using different chemicals. Details of different techniques which have been employed to characterize as prepared samples like X-Ray diffraction (XRD) technique, high resolution transmission electron microscopy (HRTEM), Fourier transfer infrared (FTIR) spectroscopy, UV-Vis spectroscopy and photoluminescence (PL) spectroscopy including their model number have been provided. Samples names and their codes have also been listed systematically in tabular form. Chapter 4 describes the study of lanthanides (RE3+ = Eu3+, Tb3+ and Dy3+) doped Y2O3 nanophosphors (NPs) prepared via co-precipitation method. The effect of variation in annealing temperature and doping concentration has been studied on optical and morphological properties of doped Y2O3. Moreover, Y2O3:Eu3+ (red phosphor), Y2O3:Tb3+ (green phosphor) and Y2O3:Dy3+ (orange phosphor) are three types of phosphors which are xviii different from each other according to their optical characteristics. For simplicity these three systems have been presented separately. Chapter 5 deals with the effect of alkali metal ions (Li+ , Na+ and K+ ) co-doping on optical and morphological properties of Y2O3:RE3+ (RE3+=Eu3+, Tb3+ & Dy3+) doped nanophosphors (NPs) prepared via co-precipitation method. Enhancement of the luminescence of these phosphors further by co-doping them with alkali metal (Li+ , Na+ and K+ ) ions have been discussed in detail. Various contributing factors that help in the luminescence enhancement of lanthanide ions (Eu3+, Tb3+ & Dy3+) in the presence of alkali ions (Li+ , Na+ and K+ ) for Y2O3 (as host matrix) have also been presented systematically in this chapter. Chapter 6 describes the effect of various surface modifiers (polymers and surfactants) on optical and morphological properties of doped Y2O3 nanophosphors. Samples of doped Y2O3 prepared with and without addition of polymers have been compared so as to explain the effect of polymers on optical and morphological properties of doped Y2O3 nanophosphors. Amount of polymers (at the time of synthesis) have been varied systematically to see their effect on optical and morphological properties of doped Y2O3 nanophosphors. Effect of pH of the solution during synthesis has also been described in this chapter. Chapter 7 summarizes the results obtained from various experiments discussed in the previous chapters. Effect of various parameters (e.g. annealing temperature, doping of rare earth ions, co-doping of alkali metal ions, pH of the solution and use of surface modifiers at the time of synthesis) on optical and morphological properties of doped Y2O3 have been summarized. Results obtained from the variation of these parameters were studied in detail. Further, conclusions made from the study of these results have also been summarized in this chapter. Based on the observation of the present work, some suggestions to carry out more work in this field have been given at the end of this chapter.
Keywords: Nanophosphor; Luminiscence; LED Devices; Optical Materials